2017
DOI: 10.1098/rsta.2017.0108
|View full text |Cite
|
Sign up to set email alerts
|

The origin, history and role of water in the evolution of the inner Solar System

Abstract: One contribution of 9 to a Theo Murphy meeting issue 'The origin, history and role of water in the evolution of the inner Solar System'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Indeed, noble gases clearly show that there is a solar component in the Earth's mantle (e.g. [112]). …”
Section: Minor Contributors To Volatile Budgetsmentioning
confidence: 99%
“…Indeed, noble gases clearly show that there is a solar component in the Earth's mantle (e.g. [112]). …”
Section: Minor Contributors To Volatile Budgetsmentioning
confidence: 99%
“…Recent models of ingassing of nebular hydrogen into the magma ocean show that only 1% of water entered the planet in this way (Wu et al 2018). The current general consensus is that the Earth acquired its water inventory largely via accretion of chondritic materials (Russell et al 2017). Also, experiments of metal-silicate partitioning require the presence of a hydrous magma ocean to account for the characteristics of certain trace-elements of the Earth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the structure and dynamics of the water–olivine interface are strongly affected by the surrounding conditions such as water fugacity and temperatures. Our collective understanding of the structure, dynamics, and vibrational behavior of water on forsterite sets the stage for interrogating more complex mineral–water interactions such as the uptake, stability, and storage of water on interstellar particles as they agglomerate and evolve into larger entities, ultimately leading to protoplanet formation. Understanding interfacial water behavior in this context provides the foundation for addressing the origin and evolution of water on Earth starting from deep time. Further, this detailed knowledge of water on forsterite acts as the stepping stone to explore surface reactivity involving dissolution and alteration to new phases, such as serpentine, relevant to subaerial weathering and subsurface systems.…”
Section: Discussionmentioning
confidence: 99%